Escape of α-particle from hot-spot for inertial confinement fusion - Li, Kai; Lan, Ke (Physics of plasmas, 2019)
Escape of α-particles from a burning or an ignited burning deuterium-tritium (DT) hot-spot with temperature up to more than tens of kilo-electron-volts is very important in inertial confinement fusion, which can significantly influence not only the hot-spot dynamics but also the energy gain. In this paper, we study the α-particle escape from a burning or an ignited burning DT hot-spot by considering the modifications, including the α-particle stopping by both DT ions and electrons with their Maxwellian average stopping weights, the relativity effect on electron distribution, and the modified Coulomb logarithm of the DT-α particle collisions. As a result, the escape effect from our modified model is obviously stronger than those from the traditional models. A fitted expression is presented to calculate the escape factor, which can be applied to a burning hot-spot with a temperature of 1–150 keV and an areal density of 0.04–3 g/cm2 with an accuracy within ±0.02. Finally, we discuss the α-particle escape effect on hot-spot dynamics and thermonuclear energy gain by comparing the results with escape factors from different models.